Methane Concentrations from the WAIS Divide Ice Core (WDC06A), 60 to 11,300 ybp - Sowers, Todd A. (IEDA: US Antarctic Program Data Center, 2012)
This data set contains a high-resolution history of atmospheric methane (CH4) concentrations in parts per billion (ppb) from approximately 60 to 11,300 years before present (ybp), obtained in 2010 from the West Antarctic Ice Sheet (WAIS) Divide Ice Core WDC06A. Gas age is derived from the WDC06A-5 ice age scale. Data are available via FTP as a Microsoft Excel file (.xlsx).